Global food policy report 2024: Food systems for healthy diets and nutrition - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
Food systems and diets underpin many critical challenges to public health and environmental sustainability, including malnutrition, noncommunicable diseases, and climate change, but sustainable healthy diets have the unique potential to reshape the future for both human and planetary well-being. The 2024 Global Food Policy Report draws on recent evidence to examine the role of food systems in driving nutrition outcomes and opportunities for transforming food systems to ensure healthy diets for all.